Evaluasi Sistem Informasi Penjualan dan Piutang Dagang pada PT. LMY - Hendarti, Henny; Leonard, Leonard; Thamrin, Agus; Yohanes, Yohanes (ComTech: Computer, Mathematics and Engineering Applications, 2011)
The purpose of this research is to evaluate and test the reliability of sales and accounts receivable information system of PT. LMY in order to help overcome the problems faced by the company. The methods used are literature review and field researches such as interviews, checked-question lists, observations and analysis. Audit around the Computer is used as the audit method. The evaluation results in some discoveries of the advantages and disadvantages of the sales and account receivable information systems used, where the disadvantages allow for the potential risks. The conclusion based on the obtained evaluation results on the control of information systems sales and accounts receivable company is that any improvement is still needed, especially on the control of security management as well as boundary. Thus, it is necessary for the company to do audits regularly on sales and account receivable information system so that the information system can be more reliable.